Production of phospholipase A2 from recombinant yarrowia lipolytica biopharmaceutical application - Mokhtar, Nur'Ainun (2013)
Phospholipase A2 (PLA2) is an enzyme that catalyzes the hydrolyisis of glycerophospholipids at the sn-2 position to yield the corresponding lysophospholpids and the free fatty acids. It catalytic properties which act as powerful emulsifier make it a widely used enzyme in various industrial application including laboratories, cosmeticeuticals, food industry as well as in pharmaceutical. However, in most industries, the PLA2 used are mainly isolated from mammalian pancreas (bovine and porcine). On the contrary, it had come to an issue regarding the origin of this animal based product which are rejected due to religious concern and the risk of viral infections to the consumers. To prevail the issue, an alternative PLA2 to replace the commercially available PLA2 has been initiated. Optimization of production parameters such as temperature, initial pH, inoculums size, inducer concentration and agitation speed are investigated using Two-Level Factorial Design and Central Composite Design by Design-Expert®. From this study, the optimal conditions PLA2 production are 6% (v/v) inoculums size; agitation speed, 225 rpm; pH 5.8; temperature of 34.5oC; inducer concentration, 0.03% (v/v) in basal salt medium. A verification run and scale up of PLA2 production yield 26.22 mg/L and 19.07 mg/L respectively compared to 27.15 mg/L predicted by the model. Purification of this enzyme through freeze drying and ultrafiltration and have shown a satisfactory purification factor of 1.15 and 1.35, respectively. The enzymatic properties (optimum activity at 37oC, pH 8.0) of the recombinant produced PLA2 from Y. lipolytica in this study shows similar properties to that of commercially available PLA2 in market which indicate that this recombinant PLA2 is a good and remarkable alternative of PLA2 sources for biopharmaceutical usage especially for HALAL applications.